Study on Relationship Among Emotional Intelligence And Virtual Listening Classroom With Soundcloud - Wisnu Kala Kusumajati; Dini Fitriani (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2022)
Abstract: The research’s objective is to investigate correlation of the students’ emotional intelligence and their listening skill in virtual classroom using Soundcloud. During the pandemic, the use of that mobile enhanced-learning application permitted the students to maximize their learning with the practicality, accessibility, and discharging cost cleared up the way. The research was in correlational research method that all of data were obtained by using quantitative research. The population was twelfth grade students, it was 102 students. The sampling technique is proportional percentage sampling by 40% x population (102) = 39.20 = 40 respondents as the respondents. The result of research was the research hypothesis is accepted. It means that there is any correlation of students emotional agility on their listening. It could be seen through , significance level 0,05 is . Thus, the mean’s is the alternative hypothesis (Ha) is accepted and Null hypothesis (Ho) is rejected or students’ emotional intelligence influences their listening skill